Participación ciudadana: De la participación en la gestión a la gestión de la participación - Ramos, Andrés Cernadas; Pérez, Luca Chao; Nebot, Carmen Pineda [UNESP] (Universidad Complutense de Madrid (UCM), 2017)
The study's main objective is to analyze the evolution of citizen participation based on the following four areas: 1) whether the formation of a progressive government for four years, after the Popular Party government for over two decades, had assumed changes substantial in the area of citizen participation and if the political color or ideology of the municipal government is an explanatory element of citizen participation levels, 2 share) analyze what mechanisms are being used in local administration in Galicia to incorporate the views of the citizens in decision-making and in what areas is occurring, 3) studying political participation addressed in order to facilitate the inclusion of citizens in decision-making or otherwise see public participation as a tool of patronage to use and control; 4) finally, to account for the most significant changes in citizen participation in Galicia throughout the study and try to explain the reasons for the same period.
Citizen participation: From participation in management to the management of participation
Keywords: Citizen participation; Local democracy; Local governance; Participatory instruments; Public local management